1996
DOI: 10.1007/bf02100126
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of push-enteroscopy and long-term follow-up of patients with small bowel angiodysplasias

Abstract: Gastrointestinal angiodysplasias are the most common cause of obscure chronic digestive blood loss. Push-enteroscopy is likely to detect and to treat vascular lesions. Push-enteroscopy was performed in 83 patients (mean age 62 years) presenting with iron deficiency anemia of obscure origin. A nonrevealing preliminary evaluation included esophagogastroduodenoscopy, colonoscopy and, in 50% of the patients, small bowel barium studies. We employed a 240-cm Olympus push-enteroscope (XSIF-100), 11.3 mm in diameter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 12 publications
3
48
0
9
Order By: Relevance
“…2,3 Most angiodysplasias will never bleed, but those that do make up 5% of overt upper GI bleeds, 4 7% of overt lower GI bleeds, 5 and between 65% and 80% of lesions found in obscure GI bleeds. [6][7][8][9] Many patients with GAVE are also asymptomatic, so the prevalence in the general population is unknown, but a screening study in cirrhotic patients reported a prevalence of 12%. 10 GAVE accounts for 4% of all nonvariceal bleeds in the general population 11 and 6% of upper GI bleeds in cirrhotic patients.…”
mentioning
confidence: 97%
“…2,3 Most angiodysplasias will never bleed, but those that do make up 5% of overt upper GI bleeds, 4 7% of overt lower GI bleeds, 5 and between 65% and 80% of lesions found in obscure GI bleeds. [6][7][8][9] Many patients with GAVE are also asymptomatic, so the prevalence in the general population is unknown, but a screening study in cirrhotic patients reported a prevalence of 12%. 10 GAVE accounts for 4% of all nonvariceal bleeds in the general population 11 and 6% of upper GI bleeds in cirrhotic patients.…”
mentioning
confidence: 97%
“…[1][2][3] Small intestinal angiodysplasias are found in 30% to 40% of patients with OGIB. 4,5 Small intestinal bleeding can be detected, diagnosed, and localized by double-balloon endoscopy (DBE). 6 No consensus has been reached regarding the most effective therapeutic strategy for angiodysplasia of the small intestine.…”
Section: Abstract: Transumbilical Single-incision Laparoscopic Surgementioning
confidence: 99%
“…Patientenzahl Pathologische Befunde (%) Laundi 1998 [18] 76 26 Benz 1997 [4] 56 27 Barkin 1994 [3] 20 30 Pennazio 1995 [31] 61 41 Zaman 1998 [40] 95 41 Davies 1995 [7] 11 45 Shakel 1998 [36] 68 57 Schmit 1996 [35] 83 59 Morris 1996 [24] 39 62…”
Section: Autorenmentioning
confidence: 99%